Stability of value orientations of participants in international academic mobility programmes - Kostiuk, Tetiana; Bakhov, Ivan; Chernukha, Nadiia; Kostenko, Dmytro; Poltoratska, Alla; Omelchenko, Svitlana (Intelektual Pustaka Media Utama, 2025)
The development of the higher education system definitely involves the development of the values and meanings of an individual. Academic mobility programmes are the means of achieving this, which enable all participants of the educational process to learn the experience of other educational institutions and countries. Identify the value orientations of participants in international academic mobility programmes. The research employed method questionnaires. Descriptive analysis, dispersion analysis, and regression analysis were used for statistical processing of the results. It was found that students who participated in international academic mobility programmes are characterized by a qualitative change in value priorities, they consider the expansion of their worldview the main motivation of mobility, and the cultural and educational value as the main one. It was proved that the term of mobility, the country of residence, and motivation do not affect the students’ life values. The obtained research results can be used to expand the possibilities of academic mobility programmes, develop true European values in students, and enrich the experience. Further research may focus on identifying the competencies that can be formed or improved in the participants of international academic mobility programmes and the related means.